Two novel variants in CEP152 caused Seckel syndrome 5 in a Chinese family - Zhang, Li; Teng, Yanling; Hu, Haoran; Zhu, Huimin; Wen, Juan; Liang, Desheng; Li, Zhuo; Wu, Lingqian (Frontiers in Genetics, 2023)
Background: Seckel syndrome (SCKL) is a rare autosomal recessive inherited disorder, which is mainly characterized by intrauterine and postnatal growth restrictions, microcephaly, intellectual disability, and a typical “bird-head” facial appearance. Here, we aimed to identify the genetic etiology of a family with suspected SCKL. Methods: This study enrolled a Chinese family suspected of SCKL with their detailed family history and clinical data. We performed karyotype analysis, copy number variation sequencing (CNV-seq), and trio whole-exome sequencing (WES) to explore the genetic etiology in the proband. Furthermore, the quantitative real-time polymerase chain reaction (PCR) and reverse transcription-PCR (RT-PCR) were conducted to confirm the pathogenicity of novel variants. Results: The karyotype analysis and CNV-seq were normal in the proband. Two novel variants in CEP152, c.1060C>T (p.Arg354*) and c.1414-14A>G, were identified in the proband through trio-WES. The qPCR results showed that the total CEP152 mRNA expression levels were significantly reduced in c.1060C>T (p.Arg354*) and c.1414-14A>G compared with healthy control individuals. Moreover, aberrant skipping of exon 12 due to the non-canonical splice-site variant was revealed by RT-PCR and Sanger sequencing. Conclusion: Our findings expanded pathogenic variant spectra in SCKL and offered new insights into the pathogenicity of a non-classical splice-site variant in CEP152, which provided additional information for helping the family improve pregnancy plans in the future.